2019
DOI: 10.1016/j.imr.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of one time coffee fragrance inhalation on working memory, mood, and salivary cortisol level in healthy young volunteers: a randomized placebo controlled trial

Abstract: BackgroundOlfactory system regulates the brain which controls emotional memory. Coffee is one of the most consumed beverages in the world. Drinking coffee shows beneficial effects for mood, memory, and psychomotor performance. This work aimed to determine the effects of inhaling coffee fragrance on memory, mood, and salivary cortisol level in healthy young volunteers.MethodsEighty young males and females, aged between 18–22 years old, were randomly assigned into two groups: a placebo group inhaling scent from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our results are in line with other odors used for dental care; orange or lavender aromatherapy has been shown to improve the mood of the patients while waiting in the dental office as assessed from the self-reported questionnaires 28,29 . A recent study using coffee aroma also found that it can enhance cognitive performance in healthy volunteers 32 . To our knowledge, there is no other study on the effect of coffee aromatherapy.…”
Section: Discussionmentioning
confidence: 97%
“…Our results are in line with other odors used for dental care; orange or lavender aromatherapy has been shown to improve the mood of the patients while waiting in the dental office as assessed from the self-reported questionnaires 28,29 . A recent study using coffee aroma also found that it can enhance cognitive performance in healthy volunteers 32 . To our knowledge, there is no other study on the effect of coffee aromatherapy.…”
Section: Discussionmentioning
confidence: 97%
“… 11 A study in humans had found coffee aroma to enhance working memory and stimulate alertness although without modulation of autonomic stress responses. 12 …”
Section: Introductionmentioning
confidence: 99%